Characterization of DON in IOM derived from M. aeruginosa and its removal by sunlight/immobilized TiO2 system. Issue 51 (5th June 2015) - Liu, Cheng; Wang, Jie; Chen, Wei; Zhu, Haoqiang; Bi, Hongkai
<x xml:space="preserve">Abstract</x> Dissolved organic nitrogen (DON) is now considered as one of the most important precursors of nitrogenous disinfection byproducts (N-DBPs), and the algae cells were the main source of DON in eutrophic water sources.